Newborn screening for neuro-metabolic disorders: Strategies, clinical benefits, and prerequisites for program expansion - Mütze, Ulrike; Scharré, Svenja; Schnabel-Besson, Elena; Kuseyri Hübschmann, Oya; Hörster, Friederike; Tuncel, Ali Tunç; Kölker, Stefan; Opladen, Thomas (European journal of paediatric neurology, 2025)
Newborn screening (NBS) is a successful program of secondary prevention for rare diseases, such as neuro-metabolic diseases, enabling early identification of affected individuals and pre-symptomatic treatment. Driven by innovations in high-throughput sequencing technologies, NBS panels have continued to grow and will probably be extended further in the future. However, implementing NBS for a disease is subject to various preconditions to maximize the benefit for the affected children, while avoiding harm to the screened healthy cohort, their families and the society. Ideally, data on clinical long-term benefit of NBS and early treatment is collected prior to NBS implementation through long-term observational studies and registries. In addition, NBS should be implemented as an iteratively evaluated public health program and the data collection should be accompanied by intra-operable long-term observational studies, ideally extended in international cooperations. In this review, the current expertise in NBS, the screening strategies and possible long-term clinical benefits are presented and discussed for several neuro-metabolic diseases, including propionic acidemia and isolated methylmalonic acidemias, homocystinurias, remethylation defects, acquired cobalamin (vitamin B12) deficiency, urea cycle disorders, tetrahydrobiopterin (BH4) and primary neurotransmitter disorders, as well as lysosomal storage disorders. Given these prerequisites, several of the neuro-metabolic diseases discussed here might be part of future NBS programs worldwide.
Frau Friederike Hörster wurde fälscherweise als "Höster" eingegeben
Gesehen am 21.10.2025